Loss of mitochondrial SIRT4 shortens lifespan and leads to a decline in physical activity. - Parik, S.; Tewary, S.; Ayyub, C.; Kolthur-Seetharam, U. (Journal of Biosciences, 2018)
Mitochondrial mechanisms and pathways have recently emerged as critical determinants of organismal aging. While nuclear sirtuins have been shown to regulate aging, whether mitochondrial sirtuins do so is still unclear. Here, we report that mitochondrial dSirt4 mediates organismal aging. We establish that absence of dSirt4 leads to reduced lifespan independent of dietary inputs. Further by assaying locomotion, a key correlate of aging, we demonstrate that dSirt4 null flies are severely physically impaired with a significant reduction in locomotion. In summary, we report that mitochondrial dSirt4 is a key determinant of longevity and its loss leads to early aging.